Somatic Culture in Colombia: beginnings and transformations of the concept in 27 years of research - Gonzalez-Posada, Carlos Mauricio (Advances in Social Sciences Research Journal, 2020)
The purpose of this article is to present succinctly, how the concept of somatic culture was born in our environment, and how it has been the evolution and transformation of the concept itself, that has resulted in interdisciplinary work around the dimensions of somatic culture (sexuality-eroticism, motor expressions, health, aesthetic ideal, semiotics, work, biopolitics, emotions). The exercise allowed not only to trace the origin of the somatic culture concept, but also made it possible to cover the methodological scenario on which somatic culture has made its foray, that is, the educational and social spheres, thus allowing that during the 27 years of the group’s existence, many research and intervention projects were born, which have founded and consolidated two lines of research: somatic culture and educational context; and somatic culture and sociocultural construction.